Innovative Decision-Making with VFP-Soft Sets: A Comparative Analysis - Dalkılıç, Orhan (Fırat University, 2025)
This study delves into fundamental set properties within the framework of virtual fuzzy parameterized (VFP-)soft set theory. It provides a comprehensive examination of these properties, offering essential insights and considerations. The study also simplifies the definition of VFP-soft sets to streamline data analysis, making it more accessible and less complex. Furthermore, the paper explores the integration of two distinct approaches for parameter weighting in VFP-soft sets. Notably, the research introduces a novel decision-making algorithm grounded in VFP-soft sets and conducts a comparative analysis to evaluate its effectiveness. This work contributes to the field by enhancing the understanding of VFP-soft sets and their applications, while also providing a practical decision-making tool for real-world scenarios.

Bu çalışma sanal bulanık parametreli (VFP-)yumuşak küme teorisi çerçevesinde temel küme özelliklerini incelemektedir. Bu özelliklerin kapsamlı bir incelemesini sağlayarak temel içgörüleri ve değerlendirmeleri sunar. Çalışma aynı zamanda veri analizini kolaylaştırmak için VFP-soft kümelerinin tanımını basitleştirerek onu daha erişilebilir ve daha az karmaşık hale getiriyor. Ayrıca makale, VFP-soft kümelerinde parametre ağırlıklandırmaya yönelik iki farklı yaklaşımın entegrasyonunu araştırıyor. Özellikle araştırma, VFP-soft kümelerine dayanan yeni bir karar verme algoritması sunmakta ve bunun etkinliğini değerlendirmek için karşılaştırmalı bir analiz gerçekleştirmektedir. Bu çalışma, VFP-soft kümelerinin ve uygulamalarının anlaşılmasını geliştirerek alana katkıda bulunurken, aynı zamanda gerçek dünya senaryoları için pratik bir karar verme aracı da sağlıyor.
VFP-Esnek Kümelerle Yenilikçi Karar Verme: Karşılaştırmalı Bir Analiz
Keywords: Soft Computing; Esnek Hesaplama; Mathematical Logic; Set Theory; Lattices and Universal Algebra; Matematiksel Mantık; Kümeler Teorisi; Kafesler ve Evrensel Cebir